2004
DOI: 10.1007/s00162-004-0150-4
|View full text |Cite
|
Sign up to set email alerts
|

Sound and vorticity interactions: transmission and scattering

Abstract: Abstract.We review several aspects of the propagation of sound in vortical flows. We restrict ourselves to isothermal, humidity-free flows at low Mach number M. Since vorticity plays a major role in vortex-flow interactions we focus on vortical flows. We consider two main canonical situations. The first concerns the transmission of sound. We analyze the evolution of acoustic wavefronts as they propagate across a single vortex. The second situation addresses the scattering of sound waves by nonstationary vortic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Nevertheless, it has already been shown that the approximation of L AP = L is reasonable for flows at Mach number up to 0.1 [18]. Although the ultrasonic wave is carried out by the flow, some studies indicate that the amplitudes of these waves are not significant enough to influence the velocity profile of the fluid, causing a negligible wave-flow interaction, and the problem is considered uncoupled [23].…”
Section: Working Principlementioning
confidence: 99%
“…Nevertheless, it has already been shown that the approximation of L AP = L is reasonable for flows at Mach number up to 0.1 [18]. Although the ultrasonic wave is carried out by the flow, some studies indicate that the amplitudes of these waves are not significant enough to influence the velocity profile of the fluid, causing a negligible wave-flow interaction, and the problem is considered uncoupled [23].…”
Section: Working Principlementioning
confidence: 99%
“…Limited by kinds of conditions for theoretical considerations, it is impossible to investigate wide-ranging effects of critical quantities on the scattered waves, such as the characteristic velocity of a vortex, the acoustic wavelength, and the vortex core size. While experimental studies [28][29][30] provided a wide-ranging frequency of incident waves, there are some new difficulties, such as the acoustic measurements of the near scattered field, precise control of flow properties, and desired incident waves, which make it hard to figure out concisely what properties are responsible for a scattering phenomenon observed in an experiment. Over the past few decades, rapid developments of computer technologies and numerical methods have enabled simultaneously resolved the flow and acoustic fields, which brought a huge opportunity to improve our understanding of wide-ranging scale effects and scattering mechanisms, by directly solving Navier-Stokes equations [18,24] and linearized Euler equations [31].…”
Section: Introductionmentioning
confidence: 99%
“…Values of the vorticity parameter α = 0.5 then induce Ma ∼ 0.1, which is impossible to achieve in water because of the appearance of cavitation bubbles in the vortex core, which slow down the flow velocity. However, Ma ∼ 0.1 might be reachable with one single vorticity filament in a medium with lower sound velocities, such as air [31], second sound in superfluid helium [32], or in ultracold atomic gases [33].…”
mentioning
confidence: 99%